Olhar lento e meio ambiente:: conexões e significados muito além de Fordlândia - Cólon, Marcos (Sustainability in Debate, 2018)
“Slow Violence” is the key concept in the ecocritical thought of Rob Nixon and it has been an inspiration for the documentary Beyond Fordlândia. Slow Violence is defined as “a violence that occurs gradually and out of sight, a violence of delayed destruction that is dispersed across time and space, an attritional violence that is typically not viewed as violence at all” (NIXON, 2011).